THU0393 Estimated Glomerular Filtration Rate is Associated with Bone Fragility in the Elderly. (23rd January 2014) - Gonçalves, M. J.; Rodrigues, A.; Caetano-Lopes, J.; Lopes, A.; Vidal, B.; Raquel, E.; Sarmento, M.; Canhão, H.; Fonseca, J. E.; Vaz, F.; Monteiro, J.
Abstract : Background: Osteoporosis is frequently associated with renal disease, namely the bone metabolism disturbances caused by chronic kidney disease (CKD). Both diseases are highly prevalent in the elderly. The increased risk of fragility fractures is well demonstrated in patients with end-stage renal disease (ESRD). There is recent evidence that bone pathological changes start early in the course of CKD, but still little is known about bone disease in patients with mild/moderate renal impairment. Objectives: Our aim is to evaluate whether chronic renal disease, in stages before ESRD, is associated with bone fragility. Bone fragility was assessed considering history of fragility fracture events, 10 year risk for major osteoporotic fractures and hip fractures (FRAX), biochemical bone turnover markers (P1NP and CTX) and mechanical testing to determine bone stiffness. Methods: We studied patients admitted for hip replacement surgery. They were asked for clinical data and blood samples. Blood biomechanical studies were performed and a bone cylinder was drilled from their femoral epiphyses. Glomerular filtration rate (GFR) was estimated using Cockcroft-Gault formula; we excluded patients with obvious limitations to the application of the formula. We also excluded from the analysis patients with terminal renal impairment, with eGFR≤15ml/minute or history of renal replacement therapy. Patients with admission diagnosis of aseptic femoral head necrosis we're also excluded. Results: We included 111 patients. Mean age 74.31±10.03, 70% of subjects were female, 98% Caucasian. Fragility fracture and the score FRAX had an inverted relation with eGFR (p=0.023, and for both risks p=<0.0001). The biomarker CTX also showed an inverted relation with eGFR (p= 0.003). P1NP (p=0.056) and bone stiffness (coefficient 2.42, p=0.073) showed a trend for association with eGFR. All analysis were adjusted for age and gender. Conclusions: Renal impairment in early stages, measured by eGFR, was associated with increased bone fragility assessed by fracture events, FRAX and bone turnover and biomechanics biomarkers, after adjustment to age and sex. Improving the understanding of bone metabolism disturbances in earlier stages of chronic renal disease might prevent the development of clinical bone disease in these patients. References: Rodrigues AM, Low osteocalcin/collagen type I bone gene expression ratio is associated with hip fragility fractures. Bone. 2012 Dec;51(6):981-9. doi: 10.1016/j.bone.2012.08.129. Epub 2012 Sep 5. Iwasaki Y et al. Changes in chemical composition of cortical bone associated with bone fragility in rat model with chronickidney disease. Bone. 2011 Jun 1;48(6):1260-7. doi: 10.1016/j.bone.2011.03.672. Epub 2011 Mar 21. Disclosure of Interest: None Declared